Sartans in the treatment of arterial hypertension: focus on telmisartan and azilsartan. A review - Vadim D. Zakiev; Yulia V. Kotovskaya; Olga N. Tkacheva (Терапевтический архив, 2023)
The activity of the renin-angiotensin-aldosterone system is one of the main pathogenetic mechanisms underlying cardiovascular diseases at all stages of the cardiovascular continuum. This article discusses the role of telmisartan and azilsartan as the most powerful sartans in modern cardiology. Azilsartan and especially telmisartan have a significant organoprotection and are superior to other antihypertensive drugs in terms of lowering blood pressure. However, the effect of azilsartan on hard endpoints has not been studied while the efficacy of telmisartan on hard endpoints has been evaluated in plenty clinical trials including 3 large randomized clinical trials with several thousand patients. The article also presents calculations showing the better cost-effectiveness of telmisartan compared to azilsartan.